A Case with late onset of ambiguous genitalia - Soraya Saleh Gargari; Faezeh Azizi; Nasrin Saleh; Mir Davood Omrani (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Ambiguous genitalia is an uncommon situation that happensbetween 1 and 2 per every 1000 live births and falls under the umbrella diagnosisof disorders of sexual development. Case: In this article, we report a case of male pseudohermaphroditism withambiguous genitalia. The proband was a 12 yr old girl without any uterus orovarian tissues. Karyotype of the case is 46, XY. Genes involved in sexualdifferentiation such as AR, SRD5A2, LH, LHR, FSH, 17 B HSD and SRY geneswere sequenced in both directions. No mutations were found in these geneseither. Conclusion: It seems advisable to be cautious in similar cases, and reviseprotocol for tracing the genes involved in the patients.